Zehneria tuberifera (Cucurbitaceae), a new species from Taita Hills, Kenya - Watuma, Benjamin Muema; Wei, Neng; Melly, David Kimutai; Kipkoech, Solomon; Kirika, Paul M.; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2019)
A new plant species in the genus Zehneria (Cucurbitaceae) is here described and illustrated. The species was collected at Taita Hills tropical montane forests in Kenya, a fragment of the larger Eastern Arc Mountains biodiversity hotspot. The new species, Zehneria tuberifera, is similar to Z. oligosperma and Z. longiflora, but distinguished by its tuberous rhizome and subcoriaceous leaf blades. Furthermore, it has scattered bristles along the midrib on the adaxial surface of its young leaf blades, a shorter receptacle tube, a trilobed disk in the male flower, solitary or 2-clustered female flowers, and up-to-20-flowered and subumbelliform male inflorescences.